An Optimized Space Vector Modulation Sequence for Improved Harmonic Performance - Mehrizi-Sani, A.; Filizadeh, S. (IEEE transactions on industrial electronics (1982), 2009)
This paper proposes a method for optimization of the harmonic performance of converters under space vector modulation (SVM) control. It is shown that SVM provides a number of degrees of freedom, which make it suitable for optimization, subject to desired constraints. An objective function is defined, which seeks to minimize the most significant harmonic components of the generated waveform while keeping other harmonic components within the acceptable range outlined in the available standards. Since the formulation of the problem involves both real and integer variables, specialized optimization methods capable of handling mixed-integer variables need to be employed, and hence, a genetic algorithm optimizer is used to solve the optimization problem. Optimized SVM sequences obtained for various operating points under different sampling frequencies are shown to result in significant reduction of dominant harmonics while maintaining the waveform quality within prescribed limits.